Evaluation of the Antimicrobial and Anti-inflammatory Properties of Bacillus-DFM (Norum™) in Broiler Chickens Infected With Salmonella Enteritidis - Adhikari, Bishnu; Hernandez-Patlan, Daniel; Solis-Cruz, Bruno; Kwon, Young Min; Arreguin, Margarita A.; Latorre, Juan D.; Hernandez-Velasco, Xochitl; Hargis, Billy M.; Tellez-Isaias, Guillermo (Frontiers in Veterinary Science, 2019)
Restrictions of in-feed antibiotics use in poultry has pushed research toward finding appropriate alternatives such as Direct-Fed Microbials (DFM). In this study, previously tested Bacillus isolates (B. subtilis and B. amyloliquefaciens) were used to evaluate their therapeutic and prophylactic effects against Salmonella enterica serovar Enteritidis (S. Enteritidis) in broiler chickens. For this purpose, initial antibacterial activity of Bacillus-DFM (104 spores/g or 106 spores/g) against S. Enteritidis colonization in crop, proventriculus and intestine was investigated using an in vitro digestive model. Furthermore, to evaluate therapeutic and prophylactic effects of Bacillus-DFM (104 spores/g) against S. Enteritidis colonization, altogether 60 (n = 30/group) and 30 (n = 15/group) 1-day-old broiler chickens were randomly allocated to either DFM or control group (without Bacillus-DFM), respectively. Chickens were orally gavaged with 104 cfu of S. Enteritidis per chicken at 1-day old, and cecal tonsils (CT) and crop were collected 3 and 10 days later during the therapeutic study, whereas they were orally gavaged with 107 cfu of S. Enteritidis per chicken at 6-day-old, and CT and crop were collected 24 h later from two independent trials during the prophylactic study. Serum superoxide dismutase (SOD), FITC-d and intestinal IgA levels were reported for both chicken studies, in addition cecal microbiota analysis was performed during the therapeutic study. DFM significantly reduced S. Enteritidis concentration in the intestine compartment, and in both proventriculus and intestine compartments as compared to the control when used at 104 spores/g and 106 spores/g, respectively (p < 0.05). DFM significantly reduced FITC-d and IgA as well as SOD and IgA levels (p < 0.05) compared to the control in therapeutic and prophylactic studies, respectively. Interestingly, in the therapeutic study, there were significant differences in bacterial community structure and predicted metabolic pathways between DFM and control. Likewise, phylum Actinobacteria and the genera Bifidobacterium, Roseburia, Proteus, and cc_115 were decreased, while the genus Streptococcus was enriched significantly in the DFM group as compared to the control (MetagenomeSeq, p < 0.05). Thus, the overall results suggest that the Bacillus-DFM can reduce S. Enteritidis colonization and improve the intestinal health in chickens through mechanism(s) that might involve the modulation of gut microbiota and their metabolic pathways.